Efficient synthesis and tailoring of magnetic and dielectric properties of Pb‐free perovskite‐like ABX3 metal‐organic frameworks. Issue 8 (18th July 2016) - Abhyankar, Nandita; Lee, Minseong; Foley, Megan; Choi, Eun Sang; Strouse, Geoffrey; Kroto, Harold W.; Dalal, Naresh S.
Abstract : Perovskite‐like metal‐organic frameworks (MOFs) are hybrid materials of high interest for their potential in information storage technology, as Pb‐free substitutes for the widely used lead zirconate titanate (PZT) family of multiferroics. We report here a new, microwave‐assisted method of synthesis for perovskite‐like MOFs, which exploits the advantages of rapid and volumetric heating by microwaves in order to achieve synthesis within minutes, compared to days required by previously reported methods. The preliminary results demonstrate a broad control over the size and morphology of the products, by minor changes in the reaction conditions. An investigation of the effects of size and morphology on the magnetic and dielectric properties is presented here. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Perovskite‐like multiferroic metal‐organic frameworks (MOFs) with the general formula ABX3 were synthesized by a microwave‐assisted protocol, resulting in >100‐fold increase in the efficiency of synthesis. The parameters of the synthesis were used to realize control over the size and morphology of the particles formed. The evolution of magnetic and electric properties was studied as a function of particle size.